2012
DOI: 10.1161/strokeaha.111.629923
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Perfusion Imaging With Computed Tomography and Magnetic Resonance in Acute Ischemic Stroke: Heterogeneity of Acquisition and Postprocessing Parameters

Abstract: Background and Purpose-Heterogeneity of acquisition and postprocessing parameters for magnetic resonance-and computed tomography-based perfusion imaging in acute stroke may limit comparisons between studies, but the current degree of heterogeneity in the literature has not been precisely defined. Methods-We examined articles published before August 30, 2009 that reported perfusion thresholds, average lesion perfusion values, or correlations of perfusion deficit volumes from acute stroke patients Ͻ24 hours post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 8 publications
1
41
0
5
Order By: Relevance
“…22 However, the interpretation of perfusion images is not easily reproducible among centers. 23 Our study demonstrates that a simple and reproducible sign (SVS) on pretreatment MR imaging may help to select patients for MT and could be integrated in future prospective comparative trials. It may be argued that GRE T2* and MR imaging are timeconsuming compared with CT.…”
Section: Discussionmentioning
confidence: 81%
“…22 However, the interpretation of perfusion images is not easily reproducible among centers. 23 Our study demonstrates that a simple and reproducible sign (SVS) on pretreatment MR imaging may help to select patients for MT and could be integrated in future prospective comparative trials. It may be argued that GRE T2* and MR imaging are timeconsuming compared with CT.…”
Section: Discussionmentioning
confidence: 81%
“…They also examined whether DWI could provide information on tissue viability by comparison with various histopathologic markers, but their assessment was limited in description of findings reported in included articles. Dani et al 33 assessed the reporting of perfusion imaging in human stroke and found a similar poor consistency between studies. Perfusion imaging coregistered with diffusion imaging is a technique for identifying the salvageable tissue (represented by the mismatch of the 2 images), which provides a hypothetical target for reperfusion therapies.…”
Section: Discussionmentioning
confidence: 99%
“…18 One of the challenges of using CTP is wide variability in the quantitative methods used for CTP analysis and poor reliability in measuring irreversible cerebral infarction. 19,20 Given this lack of standardization and validation of perfusion imaging and the fact that using imaging to guide acute stroke treatment remains unproven, the increased rates of imaging observed raise important questions about current practice.…”
Section: Discussionmentioning
confidence: 99%